Trend Postingan Selebrasi sebagai Bentuk Eksistensi Diri Generasi Muda di Sosial Media Instagram - Alna Hanana (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
This paper discusses how celebration posts are made as a form of self-existence by the younger generation, especially on the Instagram platform. The young generation in question is users aged 18-30 years, where the need for recognition and acceptance is still substantial. They are also undergoing many phases of change from adolescence to adulthood. While the celebration moments referred to in this paper include birthdays, graduations, and weddings. This study uses a qualitative method with a case study approach—data obtained by interview, observation and documentation techniques. The research findings were analysed with the social construction theory of reality. The research findings show that there are many celebrations celebrated by young people as a form of self-existence, where each celebration has different distinctive attributes. Celebration posts as a form of self-existence are not only done by people who are celebrating the event but also by friends and relatives who congratulate them. The state of posting is also done more in the Instagram story feature. The value of self-existence and the form of recognition to be achieved include showing love, attracting attention, showing stability, showing contemporary values, and showing popularity